Primary and Secondary Prophylaxis of Gastrointestinal Bleeding in Children with Portal Hypertension: A Multicenter National Study by SIGENP - Naire Sansotta; Paola De Angelis; Daniele Alberti; Fabiola Di Dato; Serena Arrigo; Matteo Bramuzzo; Benedetta Calcaterra; Mara Cananzi; Maurizio Cheli; Andrea Chiaro; Francesco Cirillo; Mara Colusso; et al. (Children)
Background/Objectives: Portal hypertension (PH) is a common complication in children with chronic liver diseases. Primary and secondary prophylaxis of variceal bleeding in these patients remains controversial. Our study aims to evaluate the management of gastrointestinal (GI) varices in children with PH in Italy. Methods: A questionnaire was sent to 21 major pediatric hepatology centers. It included 34 questions referring to the medical, endoscopic, radiological, and surgical management of GI varices. Results: Out of 21 centers, 16 returned a completed questionnaire (survey response rate 76%) with a high level of completeness. A total of 1206 children with PH were under follow-up. Splenomegaly associated with hypersplenism was the main indication for endoscopic surveillance in all centers (100%). Primary prophylaxis was performed with endoscopy plus non-selective beta-blockers (NSBBs) in 50%, endoscopy alone in 38%, and NSBBs alone in 12%. All centers managed acute variceal bleeding with endoscopy within 24 h, acid suppression, and octreotide infusion. Secondary prophylaxis of variceal bleeding was conducted using endoscopy (100%) and NSBBs (87%). Transjugular intrahepatic portosystemic shunt (TIPS) was considered a good option when endoscopic treatment failed in 94% of centers. Conclusions: In Italy, there is broad consensus among centers regarding the management of gastrointestinal varices in children with portal hypertension. All participating centers endorsed the use of endoscopic screening for children presenting with clinical signs of portal hypertension. Nonetheless, further research is essential to establish evidence-based guidelines and to improve overall quality of care.